Avaliação do Programa Prêmio Escola Nota Dez no contexto de colaboração entre escolas públicas municipais do estado do Ceará - Silva, Danielle Abreu (2024)
The "Prêmio Escola Nota Dez" (PENdez) is an educational policy that rewards up to 150 (one hundred and fifty) public schools with the best results and provides pedagogical and financial support to schools with the lowest results presented in the SPAECE assessments. Thus, it can be considered as an inducing policy for the improvement of the quality of education offered by participating schools whose results in the assessments were the lowest and unsatisfactory. This qualitative research aimed to evaluate the results obtained from PENdez under the collaboration regime - administrative, pedagogical, and financial - considering a school supported in the 5th year of Elementary Education, located in the municipality of Maracanaú, from 2017 to 2019. The research methodology included bibliographic analyses of articles and theses, document analyses, such as laws, decrees, and data reports elaborated by SEDUC/CE, and interviews, from the perspective of an in-depth evaluation. For data collection, open interviews were conducted with the school principal, teachers, and a technician from the Municipality's Education Department (SME). The collected data indicate that the pedagogical processes of the school are reoriented by the standardized test of the Permanent System of Assessment of Basic Education of Ceará (SPAECE), guiding what, how, and why to teach. In the view of the principal and teachers, it was common to consider the "Prêmio Escola Nota Dez" as a proactive initiative that has been generating movement in the daily life of educational institutions around an improvement in students' academic performance. In addition to this movement, we also found that even with the technical-pedagogical cooperation between the school with low performance and the school awarded with good performance, the impact was insufficient regarding the improvement of the educational results of the school under study; the social context and the reality in which the supported school is inserted are among the factors pointed out by the interviewees that negatively contribute to the teaching and learning process, as well as the lack of more targeted municipal public policies that can also affect this situation.